Kedudukan Hukum dan Hak Mewaris Terhadap Anak Hasil Inseminasi Buatan Dalam Perspektif Hukum Waris - Fernando Benito Alexander Mone Kaka; Lanny Kusumawati (LPPM Universitas Ekasakti Padang, 2024)
: In reality, not all marriages can produce offspring, so various methods are used to obtain offspring, one of which is artificial insemination from sperm donated by another person. This then raises a big question mark regarding the inheritance status of children born from sperm donation. The research method used is normative juridical with a statutory approach and also a conceptual approach. The results of this study show that children resulting from artificial insemination using a sperm donor have full rights to inherit from their parents on the basis of mutual agreement between the husband and wife to include the child resulting from insemination via a sperm donor into their marriage, so that the child is considered a biological child. (legitimate child). Apart from that, children resulting from artificial insemination also have the right to inherit from their biological father, but this must be done by obtaining recognition and approval first.